1997
DOI: 10.1097/00132586-199706000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Inhibition of Angiotensin-Converting Enzyme Improves Systemic and Renal Haemodynamic Changes During Aortic Abdominal Surgery

Abstract: SummaryWe studied 22 patients undergoing aortic surgery, allocated randomly to receive, before induction of anaesthesia, a single i.v. dose of enalapril 50 g kg 91 or saline. During infrarenal aortic crossclamping, we observed similar reductions in oxygen uptake in the two groups, despite greater systemic oxygen delivery in enalapril-treated patients; angiotensin-converting enzyme inhibition prevented the reduction in cardiac output and attenuated the decrease in glomerular filtration. Changes in glomerular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…7 The calculations indicated that, to show a difference greater or equal to 1.2 standard deviation with a power of 90% and a significance of level of 5%, 16 patients should be evaluated in each group.…”
Section: Discussionmentioning
confidence: 99%
“…7 The calculations indicated that, to show a difference greater or equal to 1.2 standard deviation with a power of 90% and a significance of level of 5%, 16 patients should be evaluated in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Experience suggests that control of blood pressure can be difficult in these patients and there have been reports of low vascular resistance on cardiopulmonary bypass (CPB) [6] in addition to case reports using angiotensin for patients in whom phenylephrine had failed [7]; however, this has been refuted by others [8]. Furthermore, it has been demonstrated that renal function may be preserved in abdominal aortic surgery using ACEIs [9].…”
Section: Introductionmentioning
confidence: 99%
“…enalaprilat improves renal perfusion during surgery, and this effect is sustained up to the seventh day after surgery. The doses of enalaprilat used in the present study were expected to suppress circulating levels of angiotensin II: doses of enalaprilat ranging from 10 to 30 mg kg ±1 produce marked inhibition (>90%) of plasma angiotensin-converting enzyme activity for 6 h. 9 In vitro measurements of angiotensin-converting enzyme inhibition or plasma angiotensin II concentration were not done. However, there was indirect but strong evidence of RAS blockade in the ACEI group in the hormonal pro®le found in this study.…”
Section: Discussionmentioning
confidence: 99%